Exploiting Faster-Than-Nyquist Signaling for MIMO Covert Communications: A Low-Complexity Design - Zhang, Yuchen; Ning, Boyu; Ni, Wanli; Wang, Jianquan; Tang, Wanbin; Niyato, Dusit (IEEE transactions on vehicular technology, 2024)
In this article, we present an investigation into the use of faster-than-Nyquist (FTN) signaling in multiple-input multiple-output (MIMO) covert communications with a multi-antenna warden. We formulate an optimization problem to maximize the covert rate subject to the covertness and transmit power constraints. Due to the dimensional expansion of variables, solving the formulated problem by conventional convex optimization method incurs unaffordable computational overhead. To circumvent this issue, we propose a low-complexity linear precoding and equalization method to nullify the energy leakage towards the warden while decoupling the MIMO FTN signaling into independent substreams simultaneously, and allocate the power by a new scaled water-filling approach. Numerical results validate the superiority of FTN signaling in MIMO covert communications over the Nyquist counterpart, and also show the effectiveness of our proposed scheme, which merely causes minor performance loss compared to the optimal baseline.